Research on fabrication method for floating structures using general photolithography with high versatility. (25th October 2021) - Horade, M; Yamada, K; Yamawaki, T; Yashima, M
Abstract: This research reports a micro-fabrication method for plastic microscale structures. Although a stepped shape, such as a cantilever, can be fabricated by micro electro mechanical systems (MEMS) deep etching technology, its disadvantages include the complicated fabrication process and its limited utilization with silicon only. Therefore, in this study, with an aim to address the aforementioned problems, we have realized the fabrication of a multi-stage structure using just a general photolithography process with high versatility. Specifically, it can be manufactured using only SU-8 resist and AZ resist, which are often used in the MEMS process. The AZ resist has the advantage of dissolving in the developer of the SU-8 resist, whether exposed or non-exposed. Thus, the sacrificial layer of AZ resist can be implemented with the SU-8 developer, thereby eliminating the need for dangerous chemicals such as hydrofluoric acid, which is used to etch silicon oxide. Herein, we have derived the optimum conditions by considering in advance the thickness of the AZ resist, the time taken to be etched in SU-8, and the desired features. Based on these optimum processing conditions, the structure could be suspended only in the region where the hole array was patterned. Although methods of using AZ resist as a sacrificial layer and floating SU-8 have been reported, in this study, both floating and fixed structures could be simultaneously fabricated by photolithography only. Accordingly, we successfully manufactured a gear structure and a MEMS sensor, both of which have floating and fixed structures. The above structures are made of highly transparent SU-8 on a glass substrate; hence, they are easily observable with a microscope. The reason for the widespread use of polydimethylsiloxane micro-channels is that they are transparent materials that can be observed under a microscope and fabricated by simple photolithography of the SU-8 resist, enabling non-microfabrication specialists to enter this field. These findings have the potential to form the foundation for developing new biochemical tests, such as actuators and sensors driven under a microscope.